Concepções de cultura no ensino de línguas: reflexões para a formação professores - Salomão, Ana Cristina Biondo [UNESP] (Universidade Estadual de Maringa, 2017)
The increasing intercultural communication through digital technologies in the world today makes us reflect on the need to rethink the relationship between language, culture and society in language teacher education. In this article, we discuss some of the results of a qualitative research conducted in the context of the 'Teletandem Brazil', Unesp, in a continuing education course for foreign language teachers of public schools. The results show a tendency of teachers to treat culture as a body of knowledge about the products, practices and perspectives of a people, usually associated with a homogeneous, static and conflictfree nation-state. The impacts of these results for language teacher training point to the need for a review of the knowledge base of teacher education with regard to teaching and learning culture in the foreign language classroom, in order to dissociate it from the idea of a homogeneous, transparent and fixed body of knowledge.
Conceptions of culture in language teaching: Reflections for teacher education
Keywords: Cultural component; Digital technology; Foreign language teaching and learning; Language teacher education; Teletandem